Phonological Analysis of Reading Variations Al-Insyirah to the Participants of the Mu'allimil Qur'an (MMQ) Malang - Husna, Indah Khotimatul; In'amuzzahidin, Muhammad (IJoIS: Indonesian Journal of Islamic Studies, 2025)
The accuracy of Qur’anic recitation is an essential prerequisite, as errors in the articulation of letters, vowel length, and the application of tajwid rules may reduce the quality of recitation and affect the learning process in Qur’anic education institutions (TPQ). The phenomenon of recitation variation is still found among teachers and participants of Qur’anic recitation training, including those in the Majelis Mu’allimil Qur’an (MMQ) Malang Branch, which applies the Qiraati method. This study aims to analyze the phonological variations in the recitation of QS. Al-Insyirah verses 3–7 among MMQ participants and to explain the role of MMQ training in correcting these variations. The research employs a descriptive qualitative method, with data collected through observation of training sessions, audio recordings of recitation, interviews with instructors and participants, and documentation. The findings indicate that recitation variations mainly occur in the accuracy of makhraj and sifat al-huruf, consistency in applying the rules of nun sukun/tanwin at specific letter junctions, accuracy of madd, as well as tempo and orderliness of wasl and waqf. These variations are influenced by prior recitation habits, differences in learning references, training intensity, and articulatory stability. MMQ training plays a role through recitation monitoring, direct correction (tashih), modeling of correct recitation, and guided repetition, resulting in more accurate and consistent recitation. These findings contribute to the formulation of more focused correction points and specific training recommendations to improve the quality of Qur’anic recitation among Qur’an teachers.